Aplikasi Informasi Kegiatan Webinar Berbasis WEB - Rani Khairani; Izzhan Hawary; Nida Nafila; Isra Prastiana Yannas; Khairinnisah; Syaila Fannisa; Munawir (Fakultas Teknik Universitas Samudra, 2021)
Webinars are inseparable activities from the world of education in higher education. However, there are still many webinars that hold conventionally starting from the announcement of the event, registration of participants, to the process of implementing the event. So that it feels less effective. Therefore, this application was created to make it easier to provide information to all students about the latest webinar in the University so that publications can be effective and efficient, this design can help solve problems that occur when webinars are held, such as attendance, information about presenters and others. The research method used in designing this web-based application is a field study, namely by direct observation, interviews with related parties, and also by conducting documentation to obtain the required information. In addition, the author also conducted various discussions as well as from various media containing the information needed, analyzing needs, and designing. The second stage is to build the system using the Waterfall type SDLC (System Development Life Cycle) method. The Waterfall Model provides a sequential or sequential software lifecycle approach starting from analysis, design, coding, testing, and maintenance.